Using Mental Accounting in Optimal Portfolio Selection - Khalili, Rasool; Abdi, Rasool; Rezaei, Nader; Pakmaram, Asgar (Management Strategies and Engineering Sciences, 2025)
The objective of the present study is to employ mental accounting in the selection of an optimal portfolio. This study is applied in its objective and employs a descriptive-survey method in its research methodology. The statistical population consisted of all professional accountants. Sampling was conducted using simple random sampling. A sample of 200 individuals participated. The data collection instrument was a researcher-developed questionnaire, and for data analysis, structural equation modeling and interpretive structural methods were utilized using SPSS, LISREL, and Excel software. A questionnaire comprising 46 indicators affecting mental accounting was administered to members of an expert group, and the fuzzy Delphi results indicated the elimination of six indicators (Maslow's hierarchy of needs, barriers to investment in other sectors, self-efficacy, enhancement of community health, consumption and saving patterns, investor peace of mind). Based on the results obtained from exploratory and confirmatory factor analyses, all 40 indicators were validated as factors influencing mental accounting. Subsequently, the interpretive structural model was utilized. According to the results, level 12, which includes criterion number 40, is identified as the most influential level, directly affecting the criteria at level 11. Level one is selected as the most influenced level, which comprises nine indicators. Additionally, indicators within the same level have mutual, pairwise influences on each other. Finally, to assess the model's validity and the accuracy of the findings, the member-checking strategy was employed, and its results confirmed the model's validity. Based on the results, investors should adopt a mental accounting approach for the entire portfolio and set longer-term objectives.